Screening of cherry leaf roll virus in Sambucus nigra plants in Ukraine - L. Mishchenko; A. Dunich; A. Dashchenko; N. Kozub; L. Hlushchenko (Карантин і захист рослин)
Goal. Cherry leaf roll virus (CLRV) infects naturally a wide range of herbaceous and woody plants, different species of trees, shrubs, horticultural, ornamental, weed plants and causes significant economic losses in many hosts and countries. CLRV on elderberry species was reported in Europe, USA, Iran and North America. Recently this virus has been detected in sour and sweet cherry fruit orchards in Ukraine. Testing of other hosts than Prunus was performed in Ukraine only recently. The aim of the study was to test the black elderberry plants (Sambucus nigra L.). for the presence of CLRV in the Poltava region and Kyiv regions.